Small-sided games in youth soccer: performance and behavior compared to the official match - Olthof, S. (Universität Groningen, 2019)
A small-sided game is a widely used training format in soccer. The purpose is to replicate (situations from) an official match. Adaptations in pitch size, number of players, and rules affect players` physical, technical, and tactical performance in these games and the representation for the match. Therefore, this thesis aimed to determine the relation between performance in small-sided games and the official match for elite youth soccer players.